The Effect of Incidental Consolidation on Management and Outcomes in COPD Exacerbations: Data from the European COPD Audit - Saleh, Aarash; López-Campos, José Luis; Hartl, Sylvia; Pozo-Rodríguez, Francisco; Roberts, C. Michael; European COPD Audit team (PLOS ONE, 2015)
Objective There is controversy regarding the significance of radiological consolidation in the context of COPD exacerbation (eCOPD). While some studies into eCOPD exclude these cases, consolidation is a common feature of eCOPD admissions in real practice. This study aims to address the question of whether consolidation in eCOPD is a distinct clinical phenotype with implications for management decisions and outcomes. Patients and Methods The European COPD Audit was carried out in 384 hospitals from 13 European countries between 2010 and 2011 to analyze guideline adherence in eCOPD. In this analysis, admissions were split according to the presence or not of consolidation on the admission chest radiograph. Groups were compared in terms of clinical and epidemiological features, existing treatment, clinical care utilized and mortality. Results 14,111 cases were included comprising 2,714 (19.2%) with consolidation and 11,397 (80.8%) without. The risk of radiographic consolidation increased with age, female gender, cardiovascular diseases, having had two or more admissions in the previous year, and sputum color change. Previous treatment with inhaled steroids was not associated. Patients with radiographic consolidation were significantly more likely to receive antibiotics, oxygen and non-invasive ventilation during the admission and had a lower survival from admission to 90-day follow-up. Conclusions Patients admitted for COPD exacerbation who have radiological consolidation have a more severe illness course, are treated more intensively by clinicians and have a poorer prognosis. We recommend that these patients be considered a distinct subset in COPD exacerbation.